NGS-based expanded carrier screening for genetic disorders in North Indian population reveals unexpected results - a pilot study - Kanika Singh; Sunita Bijarnia-Mahay; V. L. Ramprasad; Ratna Dua Puri; Sandhya Nair; Sheetal Sharda; Renu Saxena; Sudha Kohli; Samarth Kulshreshtha; Indrani Ganguli; Kanwal Gujral; Ishwar C. Verma (BMC, 2020)
Abstract Background To determine the carrier frequency and pathogenic variants of common genetic disorders in the north Indian population by using next generation sequencing (NGS). Methods After pre-test counselling, 200 unrelated individuals (including 88 couples) were screened for pathogenic variants in 88 genes by NGS technology. The variants were classified as per American College of Medical Genetics criteria. Pathogenic and likely pathogenic variants were subjected to thorough literature-based curation in addition to the regular filters. Variants of unknown significance were not reported. Individuals were counselled explaining the implications of the results, and cascade screening was advised when necessary. Results Of the 200 participants, 52 (26%) were found to be carrier of one or more disorders. Twelve individuals were identified to be carriers for congenital deafness, giving a carrier frequency of one in 17 for one of the four genes tested (SLC26A4, GJB2, TMPRSS3 and TMC1 in decreasing order). Nine individuals were observed to be carriers for cystic fibrosis, with a frequency of one in 22. Three individuals were detected to be carriers for Pompe disease (frequency one in 67). None of the 88 couples screened were found to be carriers for the same disorder. The pathogenic variants observed in many disorders (such as deafness, cystic fibrosis, Pompe disease, Canavan disease, primary hyperoxaluria, junctional epidermolysis bullosa, galactosemia, medium chain acyl CoA deficiency etc.) were different from those commonly observed in the West. Conclusion A higher carrier frequency for genetic deafness, cystic fibrosis and Pompe disease was unexpected, and contrary to the generally held view about their prevalence in Asian Indians. In spite of the small sample size, this study would suggest that population-based carrier screening panels for India would differ from those in the West, and need to be selected with due care. Testing should comprise the study of all the coding exons with its boundaries in the genes through NGS, as all the variants are not well characterized. Only study of entire coding regions in the genes will detect carriers with adequate efficiency, in order to reduce the burden of genetic disorders in India and other resource poor countries.